Halal Certification Guarantee for Culinary Business Actors in Sambas Regency - Firmansyah, Yuman; Muhammad Amin, Abdul Rauf; Muthiadin, Cut (Belalek, 2024)
This article discusses the opportunities for implementing halal certification to increase their economic growth. It is said that new opportunities for business actors who are benchmarks are the guarantee of halalness of products sold to consumers in attracting the business opportunities they are undergoing. Therefore, the Sambas Regency Government is always optimal and strives to develop the halal food and beverage industry in each region in order to encourage the growth of the halal industry for culinary business actors. In implementing the acceleration of the implementation of halal standards where one of the things needed is halal products, article 4 states that halal certification of a product is mandatory. To support one of the developments of the halal industry, an in-depth study is needed in this study to find out the extent of application in providing halal product assurance through halal certification for MSME food and beverage products in Sambas district. The research method used is a descriptive qualitative approach research method. Based on the results of observations that show that superior food and beverage products, culinary business actors have great potential in realizing halal product guarantees so that they have optimal potential and are found to be quite strategic and appropriate in realizing the design of the halal food and beverage industry.